A sensitive electrochemical aptasensor for detection of Aflatoxin B2 based on a polyacrylamide/phytic acid/polydopamine hydrogel modified screen printed carbon electrode. Issue 38 (20th September 2018) - Geleta, Girma Selale; Zhao, Zhen; Wang, Zhenxin
Abstract : A cost effective, environmentally friendly and disposable PAM/PA/PDA hydrogel based electrochemical aptasensor has been developed for sensitive and selective detection of Aflatoxin B2. Abstract : Herein we have developed a cost effective, environmentally friendly, and disposable electrochemical aptasensor (termed SPCE/PAM/PA/PDA/Apt) for the sensitive and selective detection of Aflatoxin B2 (AFB2) through immobilization of an AFB2 aptamer (Apt) on a conducting porous polyacrylamide/phytic acid/polydopamine (PAM/PA/PDA) hydrogel modified screen printed carbon electrode (SPCE). The porous structure of the PAM/PA/PDA hydrogel provides a high electrode surface area for the covalent immobilization of Apt as well as good conductivity. In the presence of AFB2, the conformation of immobilized Apt was changed by interaction of Apt with AFB2, resulting in the reduction of peak currents of [Fe(CN)6 ] 3/4− . Under optimized conditions, the as-developed SPCE/PAM/PA/PDA/Apt was capable of detecting AFB2 with a wide dynamic range from 0.1 pg mL −1 to 100 ng mL −1 and a low detection limit of 0.10 pg mL −1 in buffer solution. SPCE/PAM/PA/PDA/Apt also exhibits good reproducibility as well as selectivity against other mycotoxins including Aflatoxin B1 (AFB1), Aflatoxin G1 (AFG1), Aflatoxin G2 (AFG2), Fumonisin B1 (FB1) and Ochratoxin A (OTA). Moreover, the capability of SPCE/PAM/PA/PDA/Apt was demonstrated by determination of AFB2 in spiked corn extracts.